Predictors of Performance in Mathematics of Science, Technology And Engineering Students of a Public Secondary School in The Philippines - Keziah Margareth J. Macaso; Ronel Geraldizo Dagohoy (Journal of Social, Humanity, and Education, 2022)
Purpose: To fully participate in the future world, students of today should be mathematically skilled. Nowadays, mathematics backs directly and fundamentally the ways of business, health, finance, governance, and technology. Thus, this study predicts the performance in Mathematics through attitude in Mathematics, reflective thinking skills, and problem-solving skills of the Science, Technology, and Engineering (STE) students. Research methodology: This study utilized the descriptive-predictive method. It was conducted in Sto. Tomas National High School has 58 respondents. Results: There is a positive significant relationship between attitude in Mathematics, reflective thinking skills, and performance in Mathematics. However, it was revealed that there is a negative not significant relationship between problem-solving skills and performance in Mathematics. Furthermore, it was discovered that attitude in Mathematics significantly predicts performance in Mathematics. Limitations: The study is quantitative non-experimental research. The respondents are only those students who specialized in science, mathematics, and engineering. Contribution: The model that predicts the performance in Mathematics can be considered by mathematics teachers in improving the performance of STE students in Mathematics.